A serine protease inhibitor attenuates aldosterone-induced kidney injuries via the suppression of plasmin activity - Yutaka Kakizoe (Journal of Pharmacological Sciences, 2016)
Emerging evidence has suggested that aldosterone has direct deleterious effects on the kidney independently of its hemodynamic effects. However, the detailed mechanisms of these direct effects remain to be elucidated. We have previously reported that camostat mesilate (CM), a synthetic serine protease inhibitor, attenuated kidney injuries in Dahl salt-sensitive rats, remnant kidney rats, and unilateral ureteral obstruction rats, suggesting that some serine proteases would be involved in the pathogenesis of kidney injuries. The current study was conducted to investigate the roles of serine proteases and the beneficial effects of CM in aldosterone-related kidney injuries. We observed a serine protease that was activated by aldosterone/salt in rat kidney lysate, and identified it as plasmin with liquid chromatography-tandem mass spectrometry. Plasmin increased pro-fibrotic and inflammatory gene expressions in rat renal fibroblast cells. CM inhibited the protease activity of plasmin and suppressed cell injury markers induced by plasmin in the fibroblast cells. Furthermore, CM ameliorated glomerulosclerosis and interstitial fibrosis in the kidney of aldosterone/salt-treated rats. Our findings indicate that plasmin has important roles in kidney injuries that are induced by aldosterone/salt, and that serine protease inhibitor could provide a new strategy for the treatment of aldosterone-associated kidney diseases in humans.